Respuesta :

Firstly, 2x=2y-6;
That means, that we can substitude (I don`t know how that spells()
We get 3y-6=12.
12+6=18
18/3=6
Y is 6, so x is 3.
Hope that helps)))

Solving the equations x=y-3 and 2x+y=12 using substitution method we get x=3 and y=6.

What is Substitution Method?

In the substitution method we have to first solve for one variable and put that expression in the other equation to get the value. Steps to solve an equation by substitution are:

  1. Solve one equation and find the value of one variable in terms of other.
  2. Put that expression in the other equation.
  3. After solving we will get value of on variable then substitute the value of that variable in the expression found earlier to get the value of another variable also.

Solution Through Substitution Method:

We have two equations x=y-3 and 2x+y=12

Firstly we will find the value of x in terms of y which is actually given in the question already which is y-3.

Now we have to put this value in the other equation.

2(y-3)+y=12

2y-6+y=12

3y=18

y=6

The next step is to put the value of y in x=y-3 to get the value of x.

x=y-3

x=6-3

 x=3

Hence the answer of this question is x=3 and y=6

 

Here we concludes that an expression can easily be solved through substitution method. There are two more methods from which you can easily solve these type of equations which are elimination method and cross multiplication.

Learn more about substitution method at https://brainly.com/question/190818

#SPJ2